Study of Cost Overrun in Repair & Rehabilitation Projects in India - Mohtashim Ahmad Siddiqui*; Luke Judson; Sushil Kumar Solanki (International Journal of Architectural Design and Planning, 2023)
In broad sense, the word "rehabilitation" suggested putting a building back to how it was before. The specialized area of repair and rehabilitation engineering necessitates knowledge and skills that go beyond those needed for design and construction engineering. Repair and rehabilitation projects are significantly more challenging and more complicated than new construction projects. It is vital to take a methodical approach to structural deterioration, and technology management and economics should coexist in harmony. Inadequate early planning and analysis before beginning a repair activity can harm the project's success in terms of time, cost, and quality. Critical factors of cost overrun in repair & rehabilitation can be categorized into different category on the basis of their severity & importance. So, it is necessary to understand the cost impact of those cost overrun factors. Cost overruns leading to the financial crisis and hence these costs overrun factors must be identified and ranked so that they can be mitigated at very early stage. The goals of this study are to identify the critical factors that cause cost overrun in repair & rehabilitation projects through field study & expert interviews and analyze them through statistical tool (Cronbach’s alpha & Friedman test) to check reliability and significance as well as solutions to mitigate the cost overrun in Repair & Rehabilitation projects. As repair and rehabilitation projects are more complex and complicated than standard construction projects, poor estimates, a lack of condition assessment or visual inspection, and contractor incompetence by providing a lower quote than the projected cost may result in cost overruns. Analyzing the productivity, schedule, and cost for certain tasks may be effectively
Keywords: Bill of Quantities; Condition Survey; Cost Overrun; Repair & Rehabilitation